A Smart Stove System for cooking food: A study - Bhagyarekha Ujjwalganesh Dhaware; Dr. Kazi Kutubuddin Sayyad Liyakat (International Journal of Electrical Machine Analysis and Design, 2025)
Traditional cooking methods often suffer from inconsistencies, safety concerns, and a lack of real- time feedback, leading to suboptimal culinary results, potential hazards, and inefficient energy consumption. This paper introduces the design and implementation of an innovative Smart Stove System engineered to address these challenges comprehensively. Leveraging Internet of Things (IoT) principles, the system integrates an array of precise sensors (e.g., temperature, flame/gas detection, weight) with a sophisticated microcontroller, smart actuators (e.g., automated gas shut- off), and a user-friendly mobile application. This robust architecture enables automated, precision temperature regulation, real-time monitoring of cooking parameters, and proactive safety protocols such as automatic gas supply cut-off in case of leaks or unattended operation. Key features include remote monitoring and control, personalized recipe guidance with adaptive cooking adjustments, and energy consumption optimization. The proposed Smart Stove System aims to transform the culinary experience by ensuring consistent, perfectly cooked meals while drastically enhancing kitchen safety, reducing food waste, and improving energy efficiency, heralding a new era of intelligent and convenient home cooking.
Keywords: Cooking; Internet of things (IoT); Smart Stove; energy efficiency; food; sensors